-(7b-6)=2b+33

Simple and best practice solution for -(7b-6)=2b+33 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -(7b-6)=2b+33 equation:


Simplifying
-1(7b + -6) = 2b + 33

Reorder the terms:
-1(-6 + 7b) = 2b + 33
(-6 * -1 + 7b * -1) = 2b + 33
(6 + -7b) = 2b + 33

Reorder the terms:
6 + -7b = 33 + 2b

Solving
6 + -7b = 33 + 2b

Solving for variable 'b'.

Move all terms containing b to the left, all other terms to the right.

Add '-2b' to each side of the equation.
6 + -7b + -2b = 33 + 2b + -2b

Combine like terms: -7b + -2b = -9b
6 + -9b = 33 + 2b + -2b

Combine like terms: 2b + -2b = 0
6 + -9b = 33 + 0
6 + -9b = 33

Add '-6' to each side of the equation.
6 + -6 + -9b = 33 + -6

Combine like terms: 6 + -6 = 0
0 + -9b = 33 + -6
-9b = 33 + -6

Combine like terms: 33 + -6 = 27
-9b = 27

Divide each side by '-9'.
b = -3

Simplifying
b = -3

See similar equations:

| y-4=1-x | | y-4=1-x# | | 4-7.2x+2=0.8x+4.5 | | 5c+2=3c-2 | | 2+4(1-4n)=38 | | 8x+3x=0 | | (X/2)=(X-18) | | -18=-6k+4K | | -22=-7+3x | | 3+9y=-24 | | -4z+7z=-35 | | 66x+4(6-2)=5(4)+12 | | (X/2)=x-18 | | 7(p-3)=5(p-3) | | 66+4(6-2)=5(4)+12 | | 2x+13=57 | | -4x-2(-2x-1)=2 | | 2ln(2)-2ln(.50)= | | 4(6h-9)=31-5h | | 48+56+3x=132.35 | | 4x-4x+3=5 | | 7.9u-2-3.2u-10=2.8+u | | 33x+6=-8 | | 6y+60=36 | | 3x+232=2 | | 3nx2n/9= | | -5(4c+3)=-23 | | 3nx2n/9 | | 30=-6(3+7x)-(1+7x) | | (5y+6)-(3+4y)=0 | | 3n*2n/9 | | 2.7618=2.07/x |

Equations solver categories